Assessment of Atmospheric‐Pressure Guided Streamer (Plasma Bullet) Influence on Liposomes with Different Composition and Physicochemical Properties. Issue 7 (27th April 2015) - Svarnas, Panagiotis; Matrali, Sophia H.; Gazeli, Kristaq; Antimisiaris, Sophia G.
<x xml:space="preserve">Abstract</x> The role of lamellarity and composition of liposomal membranes in the degree of their disruption by plasma bullets is investigated. Multilamellar and unilamellar vesicle liposomes consisted of phosphatidylcholine, different amounts of cholesterol, and encapsulating calcein as a reporter molecule, are prepared. Plasma‐induced release of calcein from liposomes is used for evaluating the degree of plasma influence on the lipid bilayers. Presence of cholesterol in liposomal membranes below 50 mol%, results in increased disruption by the plasma, while liposomes with 50 mol% cholesterol are resistant. Addition of negative charged lipid in the liposomes (which results in vesicles with negative zeta‐potential) makes them more labile to the plasma and induces post‐treatment effects. Finally, it is clearly demonstrated that unilamellar liposomes are readily disordered by the plasma, as compared to multilamellar ones.<inline-graphic xlink:href="ark:/27927/pgj22dc9431" content-type="ppap201400218-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />